Design and Development of a Speed Control System for a Stepper Motor using the PIC18F4550 microcontroller and its interface - Romero Medina , Andrés Felipe; Mejía Muñoz, Nicolás; Blanco Cañón , Robin Alfonzo (I+ T+ C- Research, Technology and Science, 2024)
The stepper motor has been highlighted as a key component to achieve controlled and precise movements. This article focuses on the design and development of a stepper motor control system, with a subsequent application on a crane that will lift a small mass vertically. Each single aspect of the process has been examined in detail: from the selection and configuration of the 28BYJ-48 motor, to the implementation of the interfaces control such as the 4x4 matrix keypad and RS232 communication. In this system the control resides on the PIC18F4550 microcontroller. The control approach has had two modes: manual and automatic. In manual mode, the matrix keyboard has been used to allow direct interaction with the crane, adjusting parameters such as speed or direction. The automatic mode has demonstrated the ability to perform predefined movements, with a specific number of steps that ensure positioning accuracy. Overall, present study shows a comprehensive electronic control system, offering applicability in various technological areas. As research in this field progresses, this system provides a solid foundation for future improvements and optimizations in similar systems.